Control of an obstacle avoider mobile robot using image processing - Kulgu, Turgay. (Thesis (M.S.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2007., 2007)
This study investigates control of a mobile Lego robot moves towards to the specified target without hitting the obstacles with the help of image processing. An experimental set-up was designed and conducted for experiments. Additionally, most common path planning algorithms were examined and Matlab was used to make simulations of these algorithms in this study. In the light of com- parison of the simulation results, VisBug Algorithm was selected as the most suitable algorithm for our study. Finally, necessary control commands to control the Lego robot were written in Microsoft Visual C++ and, are implemented in a user interface.
Keywords: Mobile robots.; Robotics.; Image processing.; Robot vision.; Robots -- Motion -- Planning.